The Routledge companion to trust - Searle, Rosalind; Nienaber, Ann-Marie Ingrid, 1980-; Sitkin, Sim B. (Routledge companions in business, management and accounting., 2018)
In recent years, trust has enjoyed increasing interest from a wide range of parties, including organizations, policymakers, and the media. Perennially linked to turbulence and scandals, the damaging and rebuilding of trust is a contemporary concern affecting all areas of society. Comprising six thematic sections, The Routledge Companion to Trust provides a comprehensive survey of trust research. With contributions from international experts, this volume examines the major topics and emerging areas within the field, including essays on the foundations, levels and theories of trust. It also examines trust repair and explores trust in settings such as healthcare, finance, food supply chains, and the internet. The Routledge Companion to Trust is an extensive reference work which will be a vital resource to researchers and practitioners across the fields of management and organizational studies, behavioural economics, psychology, cultural anthropology, political science and sociology.